Distancing From the Past - Longing for the "Heartland": Reflections on the East German Teachers' Subjective Perception of the Wende - Dobrochna Anna Hildebrandt-Wypych (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Introduction. Institutional expediency over cultural integration, accompanied by the speed and comprehensiveness of the systemic change in East Germany marginalized the whole East German community, including one professional group of particular importance: teachers. How did they adopt to the new conditions? How did they perceive their new role in the changed social and educational system? Research Aim. The answers to these questions are based on a review and critical analysis of German empirical research on experiences of the Wende among teachers from former East Germany. Excerpts from the author's own research are also included. Evidence-based Facts. In studies of teachers' subjective perception of the Wende there appear two significant strategies compensating for their biographical and professional insecurities. One is continuity, the accompanying lack of criticism and distance from the moral evaluation of the dismantled political system, including education. The other is the turn towards the idealized image of "lost community" and "closeness and care" as opposed to the "bureaucratic mentality" in the West. Summary. East German teachers' longing for egalitarianism, for the "closeness of relations", and for the "heartland", as well as distance from moral thinking about the past, are not only an educational version of the Fromm's escape from freedom in the hardship of the transition to democracy and capitalism. They also constitute an effective means of dealing with the difficult past by gradually "taming" the experiences of life in the GDR.